Enhancing Operational Management at Cafe Rengganis through SISGANIS-Based Optimization of Raw Materials, Transactions, and Financial Reporting - Sari, Nurshadrina Kartika; Kusuma, Dedy Wijaya; Sabilirrasyad, Iqbal; Wiranto, Ferry (Image : Jurnal Riset Manajemen, 2024)
Cafe Rengganis has been facing various challenges in managing its daily operations, particularly in the areas of raw material management, transaction recording, and financial reporting. The limitations of the previously used manual system resulted in high levels of raw material wastage, slow transactions, and a time-consuming financial reporting process. To address these issues, the management decided to adopt the Rengganis Management Information System (SISGANIS), a digital-based solution designed to integrate various operational management functions to improve overall efficiency. SISGANIS offers a comprehensive approach to inventory management, real-time transaction recording, and automated and accurate financial reporting. With features that support transparency and accountability, this system aims to minimize human errors in the management of raw materials and daily transactions, while also accelerating the financial decision-making process. The use of SISGANIS allows management to access accurate data, enabling more in-depth analysis and better decision-making in a shorter amount of time. The evaluation of SISGANIS implementation shows a significant positive impact on the operational efficiency of Cafe Rengganis. Raw material wastage was reduced by 29.17%, transaction speed increased by 33.33%, and the time taken to prepare financial reports was shortened by up to 60%. These findings demonstrate that the implementation of the right management information system can provide effective solutions for small and medium enterprises (SMEs) to enhance efficiency and competitiveness in the culinary industry. The successful implementation of SISGANIS at Cafe Rengganis not only improved managerial efficiency but also provided a strong foundation for faster and more accurate data-driven decision-making.